A sustainable green electron reactive processing for fire safety of polypropylene nanocomposites. (November 2022) - Xiao, Dan; Zheng, Meng-Ting; Gohs, Uwe; Wagenknecht, Udo; Voit, Brigitte; Xiao, Xue-Qing; Wang, De-Yi
Abstract: In this work, a sustainable green electron reactive processing for fire safety of polypropylene (PP) nanocomposites was designed and developed. Effect of electron reactive processing on the morphology, fire safety and tensile properties of PP nanocomposites were characterized. The results showed that the smoke production and heat release rate of PP nanocomposites were reduced by electron reactive processing. Moreover, the total heat release and rating level of PP nanocomposite in UL-94 measurement were not reduced by electron reactive processing. Furthermore, the quality of carbon layer of PP nanocomposites via electron reactive processing in the condensed-phase was also discussed. The results suggest that electron reactive processing is a sustainable green way toward fire safety of polymer nanocomposites without any negative influence on tensile properties. Highlights: PP nanocomposite was processed by a sustainable electron reactive processing. Electron reactive processing was a green way for fire safety. Tensile properties of PP nanocomposite were not reduced at low dose.